Monitoring of landslide areas with the use of contemporary methods of measuring and mapping = Monitoring terenów osuwiskowych z wykorzystaniem współczesnych metod pomiarowych i kartograficznych - Skrzypczak, Izabela; Kogut, Janusz; Kokoszka, Wanda; Zientek, Dawid (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In recent years, there is an increase of landslide risk observed, which is associated with intensive anthropogenic activities and extreme weather conditions. Appropriate monitoring and proper development of measurements resulting as maps of areas at risk of landslides enables us to estimate the risk in the social and economic aspect.
Keywords: landslide; SOPO system; GNSS measurements; laser scanning; osuwisko; system SOPO; pomiary GNSS; skaning laserowy